Processing Water‐Medium Spinal Endoscopic Images Based on Dual Transmittance - Ning Hu; Qing Zhang (CAAI Transactions on Intelligence Technology)
ABSTRACT Real‐time water‐medium endoscopic images can assist doctors in performing operations such as tissue cleaning and nucleus pulpous removal. During medical operating procedures, it is inevitable that tissue particles, debris and other contaminants will be suspended within the viewing area, resulting in blurred images and the loss of surface details in biological tissues. Currently, few studies have focused on enhancing such endoscopic images. This paper proposes a water‐medium endoscopic image processing method based on dual transmittance in accordance with the imaging characteristics of spinal endoscopy. By establishing an underwater imaging model for spinal endoscopy, we estimate the transmittance of the endoscopic images based on the boundary constraints and local image contrast. The two transmittances are then fused and combined with transmittance maps and ambient light estimations to restore the images before attenuation, ultimately enhancing the details and texture of the images. Experiments comparing classical image enhancement algorithms demonstrate that the proposed algorithm could effectively improve the quality of spinal endoscopic images.